Basic skills and the earnings of dropouts - John H. Tyler (Brown University, Department of Economics, 2002)
This paper tests the extent to which the accumulation of basic cognitive skills, as measured by a post-schooling math test, matter for young dropouts entering today's labor market. Based on a sample of dropouts who were age 16-18 when administered a math test in the late 1990s, estimates indicate that a standard deviation increase in the test score is associated with 6.5 percent higher average earnings over the first three years in the labor market. These results are the first direct evidence that young dropouts in today's economy are not relegated to jobs where basic cognitive skills are not rewarded, and they stress the importance of skill acquisition for students who may eventually drop out.
Keywords: I20; I28; J24; 330; Human Capital; Dropouts; Low-Skilled Workers; Returns to Skills; Abbrecher; Qualifikation; Lohn; Arbeitsmarkt; USA